Sports Facilities and Equipment: Availability and Students’ Satisfaction in The Physical Education Classes - Ellen Niah Rosete; Zyrrah Grace Candelon; Akmad Gandal; Jayson A Falle; Vivencio Jr. L. Calixtro (Universitas Pendidikan Indonesia (UPI), 2022)
This study aspired to identify the available Sports Facilities and Equipment and to determine the satisfaction in using these facilities and equipment during the Physical Education (PE) class. It is in the light of this study to (1) determine the availability of sports facilities and equipment, (2) address the different levels of student’s satisfaction, and (3) provide strategies and techniques to provide efficient sports facilities and equipment for a better outcome in during PE classes. It utilized a Random Sampling Method and used adapted and modified survey questionnaires through Google forms in gathering the data needed. The questionnaire was given to 30 respondents of Bachelor of Physical Education students in Sultan Kudarat State University, ACCESS, EJC Montilla, Tacurong City, Sultan Kudarat. This study revealed that the College of Teacher Education has available sports facilities and equipment, but there are some sports like aquatics, athletics, baseball, and basketball that has not had enough equipment. The level of students’ performance in using sports facilities and equipment has a good impact on the students’ performance. The school administrators especially in the Physical Education department are encouraged to check the availability of facilities and equipment. It is highly recommended to ensure usability and upgrading of sports facilities and equipment. This study will develop alternative ways and strategies to meet the student’s needs in performing PE classes.